The Quality of Open Spaces in Campus: Perception and Social Interaction - Kustiani, Kustiani -; Rahmatika, Mellia; Nastiti, Kiara Shinta; Karolin, Ica (Jurnal Arsitektur, 2025)
This study examined three university open space case study locations: the University of Teknokrat Indonesia (UTI), the University of Bandar Lampung (UBL), and IIB Darmajaya. The purpose of this study was to evaluate the correlation between open space and the perception of social interaction of space users. This study used two methodological approaches to evaluate spatial quality: the spatial analysis method and space syntax, specifically to assess the usefulness of visibility graph analysis. As well as measuring the attributes of social interaction of users statistically by distributing questionnaires. This study concludes that the highest correlation among open space interactions is observed in the UTI campus, exhibiting a connectivity value of 7400, an integration value of 27.62, and a thorough vision analysis value of 40151. Meanwhile, the findings of perception and social interaction, based on the results of the questionnaire graph (spatial aspects and social aspects), it was found that the open space on the IIB Darmajaya campus obtained the highest scores for both aspects. Open spaces in the campus area must have spatial connectivity that is easily accessible to space users and have a dynamic open space design. This research is expected to contribute to establishing an open space design in the campus area based on the principles of spatial connectivity and social interaction.